Predicting ligand-dependent nanocrystal shapes of InP quantum dots and their electronic structures - HYERI YOO; LEE, KYEONG SEOK; Nahm, S.; Hwang, G.W.; Kim, S. (Elsevier BV, 2022)
InP quantum dots serve as solid candidates for the next-generation displays, yet their limited external quantum efficiencies have been the primary concern towards establishing self-luminous QD displays. At the heart of the problem lies our lack of understanding of how surface ligands affect the InP quantum dot properties. Here, we use density functional theory calculations to study the effect of ligand chemistry (amines, carboxylate ions, and halide ions) and coverage on the InP surface energies, equilibrium crystal shapes, and density of states. In terms of ligand chemistry, amine adsorption leads to (1 1 1)In facet-dominant octahedral Wulff shapes, while high coverage of halide results in (1 0 0)In facet-dominant cubic shapes. The computed density of states shows that the n-type defects in bare (1 1 1)In surfaces disappear upon anion adsorption, while the trap states in bare (1 0 0)In surfaces persist either with n-type or p-type upon ligand adsorption. The divergence between thermodynamically stable InP Wulff shapes and trap-suppressed InP facets call for mixed ligation strategies. ？ 2021 The Author(s)